Oxygenated glycerol derivatives as an alternative source of energy: A review - Cavalcante, Kiany Sirley Brandão; da Silva, Mitchell González Soares; Sifrônio, Francisco Sávio Mendes; Valois, Renata Rodrigues Santos; Maciel, Adeilton Pereira; de Souza Filho, Antonio Gomes; Silva, Fernando Carvalho (Eclética Química, 2014)
Due to the excessive production of crude glycerol by the Brazilian biodiesel industries, the commercial interest for glycerol derivatives has widely increased. Therefore, several methodologies have been proposed for such purpose, combining the reuse of this abundant raw material with new applications. In such context, this review summarizes a number of works focused on oxygenated glycerol derivatives production, regarding the reactions mechanisms (etherification, acetalization, esterification, and fermentation) and the physicochemical chemical properties and application. Thus, this work aims to contribute to future studies in chemical modification of crude glycerol; hence most of the scientific publications have discussed additives yielded from pure glycerol.